1970
DOI: 10.5130/csr.v17i1.1975
|View full text |Cite
|
Sign up to set email alerts
|

Death and Grief in the Landscape: Private Memorials in Public Space

Abstract: This article discusses private, informal memorialisation practices that mark scenes and sites of death in public spaces and places. It focuses on changing practices of public visibilities of death and grief – practices that render visible in a semiotic way what would otherwise be invisible or relatively unknown occurrences of death. It argues that roadside memorials and other types of informal public memorials bring to consciousness and signification spaces and places that might otherwise be perceived as death… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
19
0
1

Year Published

2013
2013
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 18 publications
(20 citation statements)
references
References 1 publication
0
19
0
1
Order By: Relevance
“…68 But this public memorial practice has recently been supplemented with smaller and more temporary memorials or shrines established in honour of the deceased at accident or crime scenes. 69 These informal memorials are collective in the sense that they are contributed to by various individuals, but are not public in the sense of requiring institutional permissions and public ceremony. Collective tributes in digital space take this one step further.…”
Section: Recommendationsmentioning
confidence: 99%
“…68 But this public memorial practice has recently been supplemented with smaller and more temporary memorials or shrines established in honour of the deceased at accident or crime scenes. 69 These informal memorials are collective in the sense that they are contributed to by various individuals, but are not public in the sense of requiring institutional permissions and public ceremony. Collective tributes in digital space take this one step further.…”
Section: Recommendationsmentioning
confidence: 99%
“…Recent studies show that commemorative displays are not limited to long‐term recovery. The emergence of roadside memorials (Reid ; Gibson ), spontaneous memorials (Haney and others ; Doss ), hurricane graffiti (Alderman and Ward ), and informal flood markers (McEwen and others 2012) have all been documented during the short‐term recovery. Rather than serve future growth or development, these grassroots commemorations perform three distinct, interlocking functions: grief work, communication, and community formation (Eyre ).…”
Section: Commemoration In Recoverymentioning
confidence: 99%
“…While obituaries have evolved to become more egalitarian in the late 20th century, as Nigel Starck (2002: xi) points out, the exclusivity of the genre has endured to the present day. Indeed, numerous studies of obituaries over the past 30 years have shown that ‘the lives and deaths of women and other publicly marginalised identity groups are … under-represented in public memorial culture’ more generally (Bytheway and Johnson, 1996; Fowler, 2007; Gibson, 2011: 147; Maybury, 1996). Therefore, as Judith Butler (2004) has argued, obituaries are a political type of representation: they are the ‘the means by which a life becomes, or fails to become, a publically grievable life, an icon for national self-recognition, the means by which a life becomes note-worthy’ (p. 34).…”
Section: The Obituary Migrates Online: Form Practice and Politicsmentioning
confidence: 99%
“…Numerous scholars have shown that, in an era of online and social media, established practices of remembrance are evolving and new ones are developing. Work by Roberts (2004, 2012), Walter (2014), Gibson (2007, 2011), Veale (2004) and Graham et al (2015) has been foundational in mapping the cultural and historical development of online memorialisation. Following on from that scholarship, online memorialisation within Facebook and Instagram has received an increasing amount of attention, especially from Brubaker et al (2013), DeGroot (2012), Marwick and Ellison (2012) and Leaver and Highfield (2016).…”
Section: The Obituary Migrates Online: Form Practice and Politicsmentioning
confidence: 99%